Art therapy with students at risk : fostering resilience and growth through self-expression - Stepney, Stella A. (Charles C. Thomas, 2010)
This updated and expanded new edition continues the theme of the first edition of providing the reader with extensive new research findings in the areas of resilience, cognitive science, neuroscience, dropout prevention and school engagement, coupled with new federal and state legislation. In addition, important trends in philosophical and theoretical models have emerged that call for a "reclaiming" of at-risk youth, reflecting the research, legislation and trends that impact the theory and practice of art therapy with diverse at-risk student populations. The book includes 19 tables, 16 illust